ショウワキチ ニ オケル チョウ テイシュウハ オンパ ノ カンソク 1969 1970 - 鈴木, 裕; スズキ, ユタカ; SUZUKI, Yutaka (国立極地研究所, 1971)
P(論文) From 1969 to 1970, infrasonic waves are detected by a system of seven microphones placed in the vicinity of Syowa Station on the East Ongul Island, Antarctica. The period of these waves was usually 20 to 300s, but occasionally waves with a period of more than 600s were recorded. Waves with a period of several seconds were rarely recorded. The pressure ranges from 1 to 10 dynes・cm^<-2> for the waves with a period of 20 to 100s, and the waves of several hundred seconds in period are more than several tens dynes・cm^<-2>. The waves of 20 to 100s are correlated with the geomagnetic activity. departmental bulletin paper